ClNAC84 interacts with ClMIP to regulate the cell cycle and reduce the size of Chrysanthemum lavandulifolium organs - Gao, Ri; Wang, Haibin; Qi, Xiangyu; Zhu, Lu; Yang, Xiaodong; Chen, Sumei; Jiang, Jiafu; Wang, Zhenxing; Chen, Fadi (Frontiers in Horticulture, 2022)
The NAC transcription factor is plant-specific proteins and one of the largest families of transcription factors in plants. NAC proteins are involved in various aspects of plant growth and development, but little is known about how NAC proteins regulate the cell cycle. Here, we characterized ClNAC84 from Chrysanthemum lavandulifolium (an NAC transcription factor). ClNAC84 overexpression in chrysanthemum resulted in a semi-dwarf phenotype with shorter plant height, smaller leaf size, and smaller flower size than wild-type plants. The number of cells in the S phase during the cell cycle was less in ClNAC84-overexpression transgenic chrysanthemum than in wild-type chrysanthemum. This indicates that ClNAC84 overexpression can induce cell cycle arrest at the S and G2 phases. To elucidate the ClNAC84 regulatory network, ClMIP protein was shown to interact with ClNAC84 in vitro and in vivo. ClMIP overexpression in chrysanthemum also resulted in dwarfism and decreased cell numbers, and the expression level of ClKRP5 was higher in transgenic chrysanthemum than in wild-type plants. We also found that ClMIP can bind to the promoter of ClKRP5. Our data indicate that the interaction between ClNAC84 and ClMIP may promote ClKRP5 expression and inhibit S and G2 phases of the cell cycling.